High-performance near-field electromagnetic wave attenuation in ultra-thin and transparent graphene films. (11th January 2017) - Kang, Junmo; Kim, Donggyun; Kim, Youngsoo; Choi, Jae-Boong; Hong, Byung Hee; Kim, Sang Woo
Abstract: Ultra-thin and transparent electromagnetic interference (EMI) shielding and absorbing materials are in increasing demand for near-field electromagnetic wave attenuation in transparent electronic devices that get thinner and lighter. Here, we report chemical-doped and undoped graphene as the thinnest and transparent shield for high-performance near-field electromagnetic wave attenuation. The electromagnetic loss characterization demonstrate that a single layer graphene film exhibits a giant magnetic field transmission loss normalized to the film thickness that is at least two orders of magnitude higher than those of conventional EMI shielding and absorbing materials, which is attributed to the outstanding magnetic field mirroring in graphene. The doped and double-layer graphene films exhibit superior power and transmission losses than the commercial transparent indium tin oxide shield over the frequency range from 0.1 GHz to 6 GHz. The high-performance near-field electromagnetic wave attenuation in graphene enables broad range applications such as futuristic transparent display devices.